Complex wake-induced vibration of aligned hangers behind tower of long-span suspension bridge. (January 2020) - Chen, Wen-Li; Yang, Wen-Han; Xu, Feng; Zhang, Chen-Guang
Abstract: The complex wake-induced vibrations (WIVs) of four aligned hangers behind a bridge tower were numerically simulated. The aligned hangers were simplified to two-dimensional spring–mass–damperdynamic models, and the hanger collisions were described with a rigid impact model. The Newmark - β method was employed to calculate the hanger oscillations with the user-defined function embedded in the numerical Computational Fluid Dynamics (CFD) simulations. The flow fields around the bridge tower for various yaw angles were simulated first to analyse the wake velocities at the hanger point. Subsequently, the characteristics of the hanger vibrations and the correlations between the hanger vibrations and tower wake were studied. The mechanism of the hanger collisions was revealed by analysing the differences between the aerodynamic coefficients of the hangers. Finally, the changes in the characteristic size of the tower and incoming wind speed were investigated to explain the occurrence of the violent WIVs of the hangers behind the bridge tower.